Uncertain thrombophilia markers - Franchini, Massimo; Martinelli, Ida; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2016)
The development of venous thromboembolism (VTE), which includes deep-vein thrombosis and pulmonary embolism, may be associated with inherited or acquired risk factors that can be measured in plasma or DNA testing. The main inherited thrombophilias include the plasma deficiencies of the natural anticoagulants antithrombin, protein C and S; the gain-of-function mutations factor V Leiden and prothrombin G20210A; some dysfibrinogenaemias and high plasma levels of coagulation factor VIII. Besides these established biomarkers, which usually represent the first-level laboratory tests for thrombophilia screening, a number of additional abnormalities have been less consistently associated with an increased VTE risk. These uncertain causes of thrombophilias will be discussed in this narrative review, focusing on their clinical impact and the underlying pathogenetic mechanisms. Currently, there is insufficient ground to recommend their inclusion within the framework of conventional thrombophilia testing.
Keywords: Thrombophilia; venous thromboembolism; thrombophilia markers